RESEARCH OF ANALYTICAL DETERMINISTIC METHOD MULTIPLE SITE DAMAGE CASE WITH STIFFENERS EFFECT WITH COMPOUNDING METHOD - Domas Indrawijaya - Nim: 13613049, Agus
Crack flaw is one of the common cause in the structural failure of aircraft, especially on skin and plate of fuselage and wing. Multiple Site Damage (MSD) can occur when this crack flaw is on the part of the structure with array of holes. MSD can cause a significant decrease in residual strength of structure, due to the increased crack propagation because of the interaction between each cracks. Because of that, MSD structural analysis is needed on the structure that vulnerable to MSD failure, in order to be able to give the precautions before failure occurs. MSDINA is one of the programs that developed by the ITB lightweight structure laboratory, that capable to perform MSD analysis. MSDINA can estimate residual strength and propagation of cracks for the structure with array of holes. However, MSDINA still ignore the effect of stiffener, which should make the structure stronger. At this research, MSDINA is modified so that it can include the effect of stiffener. The analysis is the comparison between simulation and modeling with and without stiffener effect. The analysis consists of a comparison of the age of the structure, residual strength, crack propagation and growth, total geometry factors, and stiffener geometry factors. The case that used in this research is the lower skin panel structure of N219 aircraft with constant amplitude load spectrum, and the simulation performed by using deterministic method. The effect of the stiffener included by using compounding method, by multiplying the program output’s geometry factors with the stiffener effect’s geometry factors. Structure that analyzed by including stiffener effect has the structure age 0.98% longer than without stiffener effect. Crack propagation growth decreased significantly at the crack tip at the hole that located in the center of stiffener, up to 70%, while the crack tip at the hole that located not in the center of stiffener is only up to 8%. Stiffener effect at this case slowing down the first crack link-up by 2000 cycles. For stiffener geometry factor, the crack tip at the hole that located in the center of stiffener has the minimum value up to 0.85. As for the crack tip at the hole that located not in the center of stiffener, has minimum value up to 0.98. Overall, stiffener effect is only significant at propagation phase and only at the crack tip at the hole located in the center of stiffener. Stiffener effect in this research case did not have a significant effect at the overall result, so the stiffener effect is safe to ignore.